Antioxidant Properties of Popular Turmeric (Curcuma longa) Varieties from Bangladesh - E. M. Tanvir; Md. Sakib Hossen; Md. Fuad Hossain; Rizwana Afroz; Siew Hua Gan; Md. Ibrahim Khalil; Nurul Karim (Journal of Food Quality)
We investigated the aqueous and ethanolic extracts of different forms (local names: mura and chora) of turmeric (Curcuma longa) from the Khulna and Chittagong divisions of Bangladesh for their antioxidant properties and polyphenol, flavonoid, tannin, and ascorbic acid contents. The antioxidant activity was determined using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical-scavenging activity and ferric reducing antioxidant power (FRAP) values. The ethanolic extract of Chittagong’s mura contained the highest concentrations of polyphenols (16.07%), flavonoids (9.66%), and ascorbic acid (0.09 mg/100 g) and chora resulted in high yields (17.39%). The ethanolic extract of Khulna’s mura showed a higher DPPH radical-scavenging activity with the lowest 50% inhibitory concentration (IC50) (1.08 μg/mL), while Khulna’s chora had the highest FRAP value (4204.46±74.48 μM Fe [II] per 100 g). Overall, the ethanolic extract had higher antioxidant properties than those in the aqueous extract. However, the tannin concentration was lower in the ethanolic extract. We conclude that the turmeric varieties investigated in this study are useful sources of natural antioxidants, which confer significant protection against free radical damage.